Climate change, monsoon failures and inequality of impacts in South India. (1st December 2021) - Dagdeviren, Hulya; Elangovan, Arthanari; Parimalavalli, Ramanathan
Abstract: This article examines the structural aspects of climate vulnerabilities in the context of monsoon failures. The paper is based on a unique household survey, conducted in Tamil Nadu, India. The study uses a rural differentiation framework to interrogate unequal vulnerabilities to monsoon failures, based on measures such as Gini coefficients and Lorenz curves of monetary losses. Results show that negative consequences of climate change in general, and monsoon failures in particular, intensify pre-existing socio-economic disparities. When the rural differentiation theory is applied in a broader sense, the analysis shows that landed and farming households have greater exposure and losses. When we move beyond these aggregate categories, the revelation is that households with pre-existing disadvantages such as marginal landholders, subsistence farmers and agricultural workers are more vulnerable. Highlights: Global warming affects agriculture in South Asia in a major way through monsoon failures. Vulnerability to monsoon failures can be measured by associated monetary losses. These losses are highly unevenly distributed, pointing to significant inequality in impacts. Landless households, marginal holders and subsistence farmers have higher losses. Climate change intensifies existing structural disadvantages.